Electrokinetic behavior of conical nanopores functionalized with two polyelectrolyte layers: effect of pH gradient - Liu, Tien Juin; Hsu, Jyh-Ping (Soft matter, 2022)
The behavior of ionic current rectification of a conical nanopore functionalized with two polyelectrolyte (PE) layers via layer-by-layer deposition subject to an extra applied pH gradient is investigated theoretically. The applied pH, the electric potential, the half-cone angle of the conical nanopore, and the fixed charge densities of the PE layers are examined in detail for their influence on the ionic current rectification (ICR) behavior of the nanopore. We found that this behavior depends highly on the direction of the pH gradient, which arises because the associated electroosmotic flow plays a significant role. The mechanisms of ionic transport in the present pH asymmetric system are discussed. The results gathered reveal that the ICR behavior of a nanopore can be tuned effectively by applying an extra pH gradient. We also examine the case where two PE layers are uniformly merged into one layer. In this case, both the fixed charge density and the concentration profile are quite different from those when two PE layers are present. The behavior of ionic current rectification of a conical nanopore functionalized with two polyelectrolyte (PE) layers via layer-by-layer deposition subject to an extra applied pH gradient is investigated theoretically.